Kontribusi Hasil Belajar Teaching Factory Terhadap Budaya Kerja Siswa Kelas XI Bidang Keahlian Kuliner - Adhila, Aisyah Dewi Nur; Mariah, Siti; Setyaningsih, Rina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is descriptively to find out: 1) The contribution of teaching factory learning outcome to the work culture of class XI students in the field of culinary expertise in the Academic Year of 2022/2023, 2) The results of teaching factory learning in class XI students in the field of culinary expertise at Yogyakarta 6th State Vocational High School Academic Year of 2022/2023, and 3) Work culture of class XI students in the field of culinary expertise at State Vocational High School 6 Yogyakarta Academic Year of 2022/2023. This type of research is descriptive quantitative research. The population in this study is 142 students of class XI in the field of culinary expertise. The research sample consists of 58 students using a proportional random sampling technique with the slovin formula. Data collection uses questionnaires and documentation. Testing the validity of the instrument using the product moment correlation with n = 30 of 20 statement items and obtained 17 valid items and 3 failed items (No. 3, 4, and 8), the reliability test used Cronbach's Alpha on the student work culture variable (Y) with a value coefficient 0.824. The data analysis technique uses descriptive analysis techniques and product moment correlation which is preceded by a prerequisite test, namely the normality test and linearity test. The results of the study show that (1) there is a contribution between teaching factory learning outcomes on the work culture of class XI students in the field of culinary expertise at SMK Negeri 6 Yogyakarta for the Academic Year of 2022/2023 with a determinant coefficient calculation of 0.117. This is indicated by the results of the value of r count = 0.342 > r table = 0.254, (2) The results of teaching factory learning in class XI in culinary expertise at SMK Negeri 6 Yogyakarta for the 2022/2023 academic year are included in the good category with a relative frequency of 98.3%, (3) The work culture of class XI students in the field of culinary expertise at SMK Negeri 6 Yogyakarta for the Academic Year of 2022/2023 is included in the high category with a relative frequency of 48%.